Possible Vicarious Traumatization Among Psychiatric Inpatients During the Remission Phase of the COVID-19: A Single-Center Cross-Sectional Study - Zheng, Yage; Xiao, Ling; Huang, Yonglan; Wang, Qing; Xie, Yinping; Wang, Huiling; Wang, Gaohua (Frontiers in Psychiatry, 2021)
Background Far from being a clinical disease, the COVID-19 pandemic has become a threatening social event worldwide exerting long-term impacts on human beings. Objective This study was designed to determine if and to what extent psychiatric inpatients during the remission phase of the pandemic suffered from vicarious traumatization. Method Totally 266 eligible participants from psychiatric and psychological wards in a hospital were recruited during October 26th,2020 to February 4th,2021 to finish a self-made online questionnaire consisting of Impact of Event Scale-Revised（IES-R）, Self-Rating Depression Scale (SDS), Self-Rating Anxiety Scale（SAS） , Obsessive-Compulsive Inventory-Revised (OCI-R), Pittsburgh Sleep Quality Index-Revised (PSQI-R), Social Support Rating Scale (SSRS), Beck Suicide Ideation Scale (SSI), 12-Item Short-Form Health Survey (SF-12). Meanwhile, some socio-demographics and information related to the pandemic were also recorded. Results The detection rate of vicarious traumatic symptoms(VTS) was 80.83%, including 40.98% for mild ones, 25.56% for moderate ones and 14.29% for severe ones, among whom 98.14% possessed all three phenotypes. 27.07% of the sample were considered possible vicarious traumatization(pVT). Having acquaintances infected with or died from COVID-19, worries on re-outbreak of COVID-19, a higher score of OCI-R or lower score of SF-12, and long latency of VTS were independent risk factors of pVT. Conclusion Our study showed that COVID-19 could have profound mental influences on psychiatric inpatients. It is high time we did some screening in the wards to seek for patients at risk. Keywords remission period, COVID-19, epidemiology, vicarious traumatization, inpatients.